(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Background : Valproic Acid (VPA) is an effective anticonvulsant widely used for the treatment of epilepsy in children, but there are pitfalls in VPA therapy, especially in case of various endocrine organs like thyroid. So the aim of this study was to evaluate the thyroid dysfunction in terms of subclinical hypothyroidism during Valproic Acid (VPA) therapy in children with epilepsy. Methods: The study was conducted in the Department of Paediatrics, and Shishu Bikas Kendra, Chittagong Medical College Hospital (CMCH) over one year duration on 50 newly diagnosed idiopathic epileptic children who were decided to start Valproate at the dose of 20mg/kg/day. At the same time similar number (n=50) of age and sex matched children visited the paediatric OPD for other health events(e.g. acute upper respiratory infection, Influenza like illness and Acute watery diarrhoea) other than epilepsy were included in the study as control group. Thyroid function status like serum levels of Thyroid-Stimulating Hormone (TSH) Free Triiodothyronine (FT3) and Free Thyroxin (FT4) were evaluated at baseline and after six months. Moreover, serum VPA level was also measured in children receiving valproate at follow up visit. Anti thyroid peroxidise antibody (Anti TPO ab) was checked at follow up visit in those having TSH level beyond normal reference range. After collecting all data it was analyzed by SPSS-19. Results: In the current study, cases consisted of 30(60%) male and 20(40%) female children. Male to female ratio was 1.5:1. Gender and age were matched in cases and control group (p>0.05). Most of the population in the cases were from rural areas 29(58%) and most of them 40(80%) belonged to middle class family. The mean±SD of TSH level significantly increased after six months in comparison with base line values (1.76±0.57μIU/ml vs. 2.70±1.50μIU/ml, p<0.05) and with control group at follow up visit (1.74±0.73μIU/ml vs 2.70±1.50μIU, p<0.05). On the other hand, in the control group there were no significant changes of TSH level in comparison with base line (1.82±0.55μIU vs 1.74±0.73μIU/ml, p=0.16). The mean±SD of FT4 value decreased significantly in the cases after six months though remained within normal reference range (1.24±0.27ng/dl vs1.11±0.13ng/dl, p<0.05) FT3 level remained unchanged. Five (10%) epileptic children in the cases were found to have subclinical hypothyroidism at follow up who had TSH level beyond the normal reference range. Anti thyroid peroxidase antibody was negative among them. In contrast, no one in control group was found to have TSH level beyond the normal limit. All cases were clinically euthyroid. No significant correlations were found between TSH level and serum VPA level (r2 = 0.035 p= 0.193). Conclusion: Subclinical hypothyroidism develops in children with epilepsy during VPA therapy. Proper attention should be given so that development of overt hypothyroidism can be avoided. Chatt Maa Shi Hosp Med Coll J; Vol.17 (2); Jul 2018; Page 14-20